A modified coal-based hard carbon negative electrode material and preparation method thereof, negative electrode sheet and sodium ion battery
By controlling the microporous structure of coal-based hard carbon materials through step-by-step vapor deposition, the problems of uneven pore size distribution, low capacity and low first efficiency of hard carbon negative electrode materials are solved, and a more uniform pore structure and higher electrochemical performance are achieved.
Patent Information
- Application Number
- CN202510253309.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-05
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-03-05
AI Technical Summary
The existing hard carbon negative electrode materials have problems such as uneven pore size distribution, low capacity and low first efficiency.
The micropores of coal-based hard carbon material are controlled by step-by-step vapor deposition method. By performing carbon deposition at the first temperature, the pore depth of the micropores is shallowed, and the micropore orifices are further contracted at the second temperature, reducing the formation consumption of SEI film and providing space for sodium cluster deposition.
It improves the uniformity of pore size distribution of coal-based hard carbon negative electrode materials, reduces the pore size of micropores and shallows the pore depth of micropores, solves the problems of low first efficiency and low capacity, and has simple process and convenient operation, and has good commercialization potential.
Smart Images

Figure CN119750548A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a modified coal-based hard carbon negative electrode material and a preparation method thereof, a negative electrode sheet and a sodium ion battery. Background Art
[0002] In recent years, with the continuous breakthroughs in technology, sodium-ion batteries have gradually moved towards industrialization.
[0003] Among the many negative electrode materials available for sodium-ion batteries, carbon negative electrodes have lower potential, higher capacity, stable physical and chemical properties, and low cost, making them the preferred negative electrode materials for the commercial development of sodium-ion batteries. Hard carbon materials have larger interlayer spacing, abundant defects, and nanopore structures formed by disordered stacking of graphite microcrystals, all of which become active sites for sodium ion storage, making them the most promising negative electrode materials for promoting the industrialization of sodium ions. However, today's hard carbon negative electrode materials still have problems such as uneven pore size distribution, low capacity, and low initial efficiency.
[0004] Therefore, how to solve the problems of uneven pore size distribution, low capacity, and low initial efficiency in hard carbon negative electrode materials is an important direction of current research. Summary of the invention
[0005] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a modified coal-based hard carbon negative electrode material and its preparation method, negative electrode plate and sodium ion battery. The present invention develops a method for controlling the micropores of coal-based hard carbon materials by step-by-step vapor deposition, which can not only improve the uniformity of the pore size distribution of coal-based hard carbon negative electrode materials, reduce the pore size of the micropores and shallow the pore depth of the micropores, so that the formation and consumption of the SEI film in the micropores can be reduced, and at the same time provide space for the deposition of sodium clusters in the platform area, solving the problems of low initial efficiency and low capacity of coal-based hard carbon negative electrode materials, but also the preparation method is simple in process, easy to operate, and has good commercial potential.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a method for preparing a modified coal-based hard carbon negative electrode material, the preparation method comprising the following steps: (1) The raw coal is carbonized to obtain a coal-based hard carbon material with a porous structure.
[0007] (2) The coal-based hard carbon material with a porous structure is placed in a chemical vapor deposition device, and a first carbon source gas is introduced at a first gas rate, while maintaining a constant temperature T1 at a first temperature, so that carbon deposition occurs in the micropores of the coal-based hard carbon material. Then, a second carbon source gas is introduced at a second gas rate, while maintaining a constant temperature T2 at a second temperature, so that carbon deposition occurs at the micropores of the coal-based hard carbon material. After completion, the modified coal-based hard carbon negative electrode material is obtained.
[0008] Wherein, the first gas speed is less than the second gas speed.
[0009] The present invention develops a method for controlling the micropores of coal-based hard carbon materials by a step-by-step vapor deposition method, which can not only improve the uniformity of the pore size distribution of the coal-based hard carbon negative electrode material, reduce the pore size of the micropores and shallow the pore depth of the micropores, thereby reducing the formation consumption of the SEI film in the micropores, but also provide space for the deposition of sodium clusters in the platform area, thereby solving the problems of low initial efficiency and low capacity of the coal-based hard carbon negative electrode material, and the preparation method is simple in process, easy to operate, and has good commercial potential.
[0010] Preferably, the raw coal in step (1) comprises any one of anthracite, lean coal, lean coal, coking coal, fat coal, gas coal, slightly sticky coal, non-sticky coal, long flame coal or lignite, or a combination of at least two thereof, preferably long flame coal.
[0011] Preferably, the temperature of the carbonization treatment in step (1) is 1100-1400°C, for example, it can be 1100°C, 1200°C, 1300°C or 1400°C.
[0012] In the present invention, carbonization treatment at an appropriate temperature helps coal to expel most impurities and volatiles, while forming abundant pores inside it. Under the action of high temperature, the carbon layer lattice is distorted to form a large number of disordered graphite crystals and amorphous carbon. These areas together form a "house of cards" structure of hard carbon, which is beneficial to the storage of sodium ions.
[0013] Preferably, the carbonization treatment time in step (1) is 1-10 h, for example, it can be 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h.
[0014] Preferably, the coal-based hard carbon material with a porous structure in step (1) has an average pore size of 1-4 nm, for example, 1 nm, 1.5 nm, 2 nm, 3 nm or 4 nm, and a pore volume of 0.1-0.3 cm 3 / g, for example, 0.1 cm 3 / g, 0.15cm 3 / g, 0.2cm 3 / g, 0.25cm 3 / g or 0.3cm 3 / g, etc.
[0015] Preferably, the coal-based hard carbon material with a porous structure in step (1) has a N2 specific surface area of 300-600 m 2 / g, for example, 300m 2 / g, 350m 2 / g, 400m 2 / g, 450m 2 / g、500m 2 / g, 550m 2 / g or 600m 2 / g, etc.
[0016] Preferably, the CO2 specific surface area of the coal-based hard carbon material with a porous structure in step (1) is 100-200m 2 / g, for example, it can be 100m 2 / g, 120m 2 / g, 140m 2 / g, 160m 2 / g, 180m 2 / g or 200m 2 / g, etc.
[0017] Preferably, in step (2), the first gas velocity is 10-50 mL / min, for example, 10 mL / min, 20 mL / min, 30 mL / min, 40 mL / min or 50 mL / min.
[0018] In the present invention, the first gas velocity of appropriate size helps the pyrolytic carbon to be uniformly deposited inside the micropores, so as to achieve the purpose of shallowing the pore depth. If the first gas velocity is too small, the carbon deposition rate is too low and the micropores cannot be filled; if the first gas velocity is too large, the carbon deposition rate is too large, the micropores are filled, and the pore structure disappears.
[0019] Preferably, in step (2), the second gas velocity is 100-300 mL / min, for example, 100 mL / min, 150 mL / min, 200 mL / min, 250 mL / min or 300 mL / min, etc., preferably 120-240 mL / min.
[0020] In the present invention, the second gas velocity of appropriate size helps to control the shrinkage rate of the micropore openings and prevent the deposited carbon from continuing to fill the inside of the micropores. If the second gas velocity is too small, the carbon deposition rate is too low, the openings shrink too slowly, the inside of the micropores are filled, and the pore structure disappears; if the second gas velocity is too large, the openings are quickly reduced, and then the micropores are directly closed at high deposition rates, and the pore structure disappears.
[0021] Preferably, in step (2), the first carbon source gas and the second carbon source gas each independently include any one of methane, acetylene, ethane, propane or benzene, or a combination of at least two of them.
[0022] Preferably, in step (2), the kinetic diameters of the gas molecules of the first carbon source gas and the second carbon source gas are independently 0.4-0.5 nm, for example, 0.4 nm, 0.42 nm, 0.44 nm, 0.46 nm, 0.48 nm or 0.5 nm.
[0023] In the present invention, the kinetic diameter of the gas molecules of the carbon source gas is limited to 0.4-0.5nm, and the purpose is to fill the micropores with pyrolytic carbon of the carbon source gas. When the orifice of the micropore is reduced to a size close to the kinetic diameter of the gas molecules, the gas molecules cannot enter the micropore and will modify the area around the orifice until the micropore is closed. At this time, the size of the orifice can be adjusted by adjusting the ventilation flow rate and the pyrolysis time.
[0024] Preferably, in step (2), the first temperature is 600-900°C, for example, 600°C, 700°C, 800°C or 900°C, etc., and T1 is 2-4h, for example, 2h, 2.5h, 3h or 4h, etc.
[0025] In the present invention, heating at the first temperature for a time T1 helps the carbon source gas to pyrolyze carbon and deposit it uniformly in the micropores, thereby achieving the purpose of filling the micropores and shallowing the pore depth.
[0026] Preferably, in step (2), the second temperature is 1000-1200°C, for example, 1000°C, 1050°C, 1100°C, 1150°C or 1200°C, etc., and T2 is 10-30min, for example, 10min, 20min or 30min, etc.
[0027] In the present invention, heating is performed at the second temperature for a time of T2. At this temperature, the carbon source gas is pyrolyzed quickly, and the increased gas flow rate can quickly shrink the pore opening, reduce carbon deposition in the pores, and prevent the micropores from being blocked.
[0028] Preferably, after carbon deposition in the micropores of the coal-based hard carbon material in step (2), the pore volume of the micropores is reduced to 0.02-0.06 cm 3 / g, for example, 0.02 cm 3 / g, 0.03cm 3 / g, 0.04cm 3 / g, 0.05cm 3 / g or 0.06cm 3 / g, etc.
[0029] In the present invention, the micropore volume within the above range is conducive to conveniently and intuitively judging the change of pore depth, thereby controlling the pore depth within a suitable range.
[0030] Preferably, after carbon deposition is performed at the micropore openings of the coal-based hard carbon material in step (2), the opening size of the micropores is 0.3-0.5 nm, for example, 0.3 nm, 0.35 nm, 0.4 nm or 0.5 nm.
[0031] The present invention can reduce the micropore size of coal-based hard carbon materials to 0.3-0.5nm, the process is controllable, and the pore size distribution is uniform. The micropores with reduced pore size and micropore depth prevent SEI from forming in the pores while providing a certain space for the deposition of sodium clusters in the platform area, which can solve the problems of low initial efficiency and low capacity of the material.
[0032] In the present invention, after the first ventilation, the pore volume of the micropores decreases significantly, while the specific surface area remains basically unchanged, indicating that the micropores are partially filled and the pore depth is shallowed; after the second ventilation, the pore volume of the micropores decreases slightly, while the specific surface area decreases significantly, indicating that the pore mouth is tightened, while the internal space of the micropores remains basically unchanged.
[0033] Preferably, the preparation method comprises the following steps: (a) The raw coal is crushed to a particle size D50 of 4-30 μm (for example, 4 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm or 30 μm, etc.), and then carbonized in an inert atmosphere at a temperature of 1100-1400°C, a heating rate of 1-10°C / min (for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, etc.), and a carbonization time of 1-10 h to obtain a coal-based hard carbon material with a porous structure, wherein the coal-based hard carbon material with a porous structure has an average pore size of 1-4 nm and a pore volume of 0.1-0.3 cm 3 / g, N2 specific surface area is 300-600m 2 / g, CO2 specific surface area is 100-200m 2 / g.
[0034] (b) placing the coal-based hard carbon material having a porous structure in a chemical vapor deposition device, introducing a first carbon source gas at a first gas velocity of 10-50 mL / min and an inert protective gas at a velocity of 50-150 mL / min (for example, 50 mL / min, 70 mL / min, 110 mL / min or 150 mL / min, etc.), and maintaining a constant temperature T1 at a first temperature, so that carbon deposition is performed in the micropores of the coal-based hard carbon material, and the pore volume of the micropores is 0.02-0.06 cm 3 / g, then a second carbon source gas with a second gas velocity of 100-300 mL / min and an inert protective gas (illustratively, nitrogen, argon, etc.) at a velocity of 200-500 mL / min (for example, 200 mL / min, 300 mL / min, 400 mL / min or 500 mL / min, etc.) are introduced, and the temperature T2 is maintained constant at the second temperature, so that carbon deposition is performed at the micropore openings of the coal-based hard carbon material, and the pore volume of the micropores is 0.01-0.03 cm 3 / g, the pore size of the micropores is 0.3-0.5nm, and the modified coal-based hard carbon negative electrode material is obtained after completion.
[0035] Among them, the first gas velocity is less than the second gas velocity, the kinetic diameters of the gas molecules of the first carbon source gas and the second carbon source gas are each independently 0.4-0.5 nm; the first temperature is 600-900°C, T1 is 2-4h; the second temperature is 1000-1200°C, T2 is 10-30min.
[0036] In a second aspect, the present invention provides a modified coal-based hard carbon negative electrode material, wherein the modified coal-based hard carbon negative electrode material is prepared by the preparation method described in the first aspect.
[0037] The N2 specific surface area of the modified coal-based hard carbon negative electrode material is 2-5 m 2 / g, for example, it can be 2m 2 / g, 2.5m 2 / g, 3m 2 / g, 4m 2 / g or 5m 2 / g, etc.
[0038] The CO2 specific surface area of the modified coal-based hard carbon negative electrode material is 0-10m 2 / g, for example, it can be 2m 2 / g, 4m 2 / g, 6m 2 / g, 8m 2 / g or 10m 2 / g, etc.
[0039] The preparation method provided by the present invention reduces the N2 specific surface area and CO2 specific surface area of the modified coal-based hard carbon negative electrode material, which is beneficial to improving the structural stability of the coal-based hard carbon negative electrode material, reducing the risk of pore collapse, and making it less likely to suffer structural damage or deformation when subjected to external forces or in a complex environment; at the same time, it is beneficial to reduce electron scattering and promote charge transfer rate, so that the coal-based hard carbon negative electrode material can play a better performance in the application. In addition, it is also beneficial to improve the adsorption selectivity and adsorption stability of specific substances.
[0040] In a third aspect, the present invention provides a negative electrode plate, wherein the negative electrode plate comprises the modified coal-based hard carbon negative electrode material as described in the second aspect.
[0041] It should be noted that the negative electrode plate also includes a conductive agent and a binder. For example, the conductive agent may be, for example, Ketjen black or Super P (conductive carbon black), and the binder may be, for example, PVDF (polyvinylidene fluoride), CMC (sodium carboxymethyl cellulose) or SBR (styrene-butadiene rubber).
[0042] In a fourth aspect, the present invention provides a sodium ion battery, comprising the negative electrode sheet as described in the third aspect.
[0043] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0044] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention develops a method for controlling the micropores of coal-based hard carbon materials by step-by-step vapor deposition. This method can not only improve the uniformity of the pore size distribution of coal-based hard carbon negative electrode materials, reduce the pore size of the micropores and shallow the pore depth of the micropores, thereby reducing the formation consumption of the SEI film in the micropores, but also provide space for the deposition of sodium clusters in the platform area, thereby solving the problems of low initial efficiency and low capacity of coal-based hard carbon negative electrode materials. In addition, the preparation method is simple in process, easy to operate, and has good commercial potential.
[0045] (2) The modified coal-based hard carbon negative electrode material prepared by the method provided by the present invention can obtain a first efficiency of more than 90% and a reversible specific capacity of more than 290 mAh / g. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 This is a process flow chart provided for Example 1 of the present invention.
[0047] Figure 2 This is a scanning electron microscope image of the coal-based hard carbon material with a porous structure provided in Example 1 of the present invention.
[0048] Figure 3 This is a scanning electron microscope image of the modified coal-based hard carbon negative electrode material provided in Example 1 of the present invention.
[0049] Figure 4 This is the average pore size distribution curve of the coal-based hard carbon material with a porous structure provided in Example 1 of the present invention.
[0050] Figure 5This is the nitrogen adsorption-desorption curve of the coal-based hard carbon material with a porous structure provided in Example 1 of the present invention.
[0051] Figure 6 This is the nitrogen adsorption / desorption curve of the modified coal-based hard carbon negative electrode material provided in Example 1 of the present invention.
[0052] Figure 7 This is a small-angle scattering diagram of the modified coal-based hard carbon negative electrode material provided in Example 1 of the present invention.
[0053] Figure 8 This is the first cycle charge and discharge curve of a sodium ion battery made from the modified coal-based hard carbon negative electrode material provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0054] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0055] Example 1 This embodiment provides a method for preparing a modified coal-based hard carbon negative electrode material, and its process flow chart is as follows: Figure 1 As shown, the preparation method comprises the following steps: (1) The raw coal (i.e., long flame coal) was crushed to a particle size D50 of 15 μm, and then carbonized in a nitrogen atmosphere at a temperature of 1300°C, a heating rate of 5°C / min, and a carbonization time of 5 h to obtain a coal-based hard carbon material with a porous structure. The coal-based hard carbon material with a porous structure had an average pore size of 2.5 nm and a pore volume of 0.17 cm 3 / g, N2 specific surface area is 420m 2 / g, CO2 specific surface area is 137m 2 / g.
[0056] (2) The coal-based hard carbon material with a porous structure is placed in a chemical vapor deposition device (rotary tube furnace), and a first carbon source gas with a first gas velocity of 30 mL / min and a nitrogen gas with a gas velocity of 100 mL / min are introduced, and the temperature is kept constant at a first temperature T1, so that the first carbon deposition is carried out in the micropores of the coal-based hard carbon material, and the pore volume of the micropores is 0.029 cm 3 / g, and then the second carbon source gas with a second gas velocity of 200 mL / min and the nitrogen gas of 350 mL / min were introduced, and the temperature T2 was kept constant at the second temperature, so that the second carbon deposition was carried out at the micropore openings of the coal-based hard carbon material, and the pore volume of the micropores was 0.025 cm 3 / g, the pore size of the micropores is 0.4nm, and the modified coal-based hard carbon negative electrode material is obtained after completion.
[0057] Among them, the first gas velocity is less than the second gas velocity, the first carbon source gas and the second carbon source gas are both methane, and the kinetic diameter of the gas molecules is 0.414nm; the first temperature is 750°C, T1 is 3h; the second temperature is 1100°C, T2 is 20min.
[0058] Figure 2 and Figure 3 The scanning electron microscope images of the coal-based hard carbon material with a porous structure and the modified coal-based hard carbon negative electrode material provided in this embodiment are respectively shown. By comparison, it can be seen that the surface of the material is obviously covered with a layer of deposited carbon after vapor deposition.
[0059] Figure 4 The average pore size distribution curve of the coal-based hard carbon material with a porous structure provided in this embodiment is shown. It can be seen from the figure that the average pore size distribution of the coal-based hard carbon material is 0-4nm.
[0060] Figure 5 and Figure 6 The nitrogen adsorption and desorption curves of the coal-based hard carbon material with a porous structure and the modified coal-based hard carbon negative electrode material provided in this embodiment are shown respectively. By comparison, it can be seen that after the vapor deposition modification, the coal-based hard carbon material has a specific surface area of 420 m 2 / g down to 3.5m 2 / g.
[0061] Figure 7 The small-angle scattering diagram of the modified coal-based hard carbon negative electrode material provided in this embodiment is shown. It can be seen from the figure that the pore size of the coal-based hard carbon material is 0.4nm, and the internal pore interconnected structure is still retained, which is conducive to the storage of sodium ions.
[0062] Figure 8 The first-cycle charge and discharge curve of the sodium ion battery prepared based on the modified coal-based hard carbon negative electrode material provided in this embodiment is shown. It can be seen from the figure that the sodium ion battery prepared from the modified coal-based hard carbon material has a first-cycle coulombic efficiency of up to 90.81%, and the reversible specific capacity reaches 297 mAh / g.
[0063] Example 2 This embodiment provides a method for preparing a modified coal-based hard carbon negative electrode material, the preparation method comprising the following steps: (1) Long flame coal was crushed to a particle size D50 of 4 μm, and then carbonized in a nitrogen atmosphere at a temperature of 1100°C, a heating rate of 5°C / min, and a carbonization time of 10 h to obtain a coal-based hard carbon material with a porous structure. The coal-based hard carbon material with a porous structure had an average pore size of 4 nm and a pore volume of 0.30 cm 3 / g, N2 specific surface area is 556m 2 / g, CO2 specific surface area is 177m 2 / g.
[0064] (2) The coal-based hard carbon material with a porous structure is placed in a chemical vapor deposition device, and a first carbon source gas with a first gas rate of 10 mL / min and a nitrogen gas of 100 mL / min are introduced, and the temperature is kept constant at a first temperature T1, so that the first carbon deposition is performed in the micropores of the coal-based hard carbon material, and the pore volume of the micropores is 0.057 cm 3 / g, and then the second carbon source gas with a second gas velocity of 100 mL / min and the nitrogen gas with a gas velocity of 200 mL / min were introduced, and the temperature T2 was kept constant at the second temperature, so that the second carbon deposition was carried out at the micropore openings of the coal-based hard carbon material, and the pore volume of the micropores was 0.033 cm 3 / g, the pore size of the micropores is 0.5nm, and after completion, the modified coal-based hard carbon negative electrode material is obtained.
[0065] Among them, the first gas velocity is less than the second gas velocity, the first carbon source gas and the second carbon source gas are both acetylene, and the kinetic diameter of the gas molecule is 0.446nm; the first temperature is 600°C, T1 is 2h; the second temperature is 1000°C, T2 is 10min.
[0066] Example 3 This embodiment provides a method for preparing a modified coal-based hard carbon negative electrode material, the preparation method comprising the following steps: (1) Long flame coal was crushed to a particle size D50 of 30 μm, and then carbonized in a nitrogen atmosphere at a temperature of 1400°C, a heating rate of 10°C / min, and a carbonization time of 2 h to obtain a coal-based hard carbon material with a porous structure. The coal-based hard carbon material with a porous structure had an average pore size of 3.6 nm and a pore volume of 0.112 cm 3 / g, N2 specific surface area is 315m 2 / g, CO2 specific surface area is 113m 2 / g.
[0067] (2) The coal-based hard carbon material with a porous structure is placed in a chemical vapor deposition device, and a first carbon source gas with a first gas rate of 50 mL / min and a nitrogen gas with a first gas rate of 150 mL / min are introduced, and the temperature is kept constant at a first temperature T1, so that the first carbon deposition is performed in the micropores of the coal-based hard carbon material, and the pore volume of the micropores is 0.025 cm 3 / g, and then the second carbon source gas with a second gas velocity of 300 mL / min and the nitrogen gas with a gas velocity of 500 mL / min were introduced, and the temperature T2 was kept constant at the second temperature, so that the second carbon deposition was carried out at the micropore openings of the coal-based hard carbon material, and the pore volume of the micropores was 0.017 cm 3 / g, the pore size of the micropores is 0.3nm, and the modified coal-based hard carbon negative electrode material is obtained after completion.
[0068] Among them, the first gas velocity is less than the second gas velocity, the first carbon source gas and the second carbon source gas are both methane, and the kinetic diameter of the gas molecules is 0.414nm; the first temperature is 900°C, T1 is 2h; the second temperature is 1200°C, T2 is 30min.
[0069] Example 4 The difference between this embodiment and embodiment 1 is that the first gas velocity in step (2) is 5 mL / min.
[0070] The rest of the preparation methods and parameters were the same as those in Example 1.
[0071] Example 5 The difference between this embodiment and embodiment 1 is that the first gas velocity in step (2) is 80 mL / min.
[0072] The rest of the preparation methods and parameters were the same as those in Example 1.
[0073] Example 6 The difference between this embodiment and embodiment 1 is that the second gas velocity in step (2) is 80 mL / min.
[0074] The rest of the preparation methods and parameters were the same as those in Example 1.
[0075] Example 7 The difference between this embodiment and embodiment 1 is that the second gas velocity in step (2) is 400 mL / min.
[0076] The rest of the preparation methods and parameters were the same as those in Example 1.
[0077] Example 8 The difference between this embodiment and embodiment 1 is that the first temperature in step (2) is 500°C.
[0078] The rest of the preparation methods and parameters were the same as those in Example 1.
[0079] Example 9 The difference between this embodiment and embodiment 1 is that the first temperature in step (2) is 1000°C.
[0080] The rest of the preparation methods and parameters were the same as those in Example 1.
[0081] Example 10 The difference between this embodiment and embodiment 1 is that the second temperature in step (2) is 900° C.
[0082] The rest of the preparation methods and parameters were the same as those in Example 1.
[0083] Embodiment 11 The difference between this embodiment and embodiment 1 is that the second temperature in step (2) is 1300° C.
[0084] The rest of the preparation methods and parameters were the same as those in Example 1.
[0085] Comparative Example 1 The difference between this comparative example and Example 1 is that in step (2), the first gas velocity is 300 mL / min, so that the first gas velocity is greater than the second gas velocity.
[0086] The rest of the preparation methods and parameters were the same as those in Example 1.
[0087] Comparative Example 2 The difference between this comparative example and Example 1 is that the first carbon source gas is not introduced in step (2), that is, the first carbon deposition is not performed.
[0088] The rest of the preparation methods and parameters were the same as those in Example 1.
[0089] Comparative Example 3 The difference between this comparative example and Example 1 is that the second carbon source gas is not introduced in step (2), that is, the second carbon deposition is not performed.
[0090] The rest of the preparation methods and parameters were the same as those in Example 1.
[0091] Performance Testing The modified coal-based hard carbon negative electrode material provided in the above embodiment and comparative example is made into a negative electrode sheet, and then assembled with a positive electrode sheet, a separator and an electrolyte to obtain a sodium ion battery. The specific steps include: The modified coal-based hard carbon negative electrode material, conductive carbon black, sodium carboxymethyl cellulose, and styrene-butadiene rubber are mixed in solvent water in a mass ratio of 93:2:2:3 to obtain a negative electrode slurry, which is then coated on a copper foil and dried to obtain a negative electrode sheet; the negative electrode sheet, the diaphragm (i.e., polyethylene diaphragm), and the positive electrode sheet (i.e., sodium sheet) are stacked in sequence, and the electrolyte (i.e., 1 mol / L NaPF6 (EC:DEC=1:1)) is injected, and the 2032-type button battery is assembled in a glove box with an argon atmosphere and then sealed to obtain a sodium ion battery.
[0092] The sodium ion battery was subjected to first efficiency and capacity performance tests under the following test conditions: the current density was 50 mA / g, i.e. 0.1 C, and the test recorded its first cycle coulombic efficiency and reversible specific capacity, where the reversible specific capacity refers to the first cycle charge specific capacity, and the first efficiency refers to the first cycle charge specific capacity / discharge specific capacity.
[0093] The test results are shown in Table 1.
[0094] Table 1
[0095] analyze: As can be seen from Table 1, the method developed in the present invention can improve the uniformity of the pore size distribution of coal-based hard carbon negative electrode materials, reduce the pore size of the micropores and shallow the pore depth of the micropores, so that the formation consumption of the SEI film in the micropores can be reduced, and at the same time provide space for the deposition of sodium clusters in the platform area, thereby solving the problems of low initial efficiency and low capacity of coal-based hard carbon negative electrode materials.
[0096] It can be seen from Examples 1 and 4-5 that if the first gas velocity is too small, the amount of carbon deposition in the micropores is insufficient, the pore volume does not change significantly, and the pore depth cannot be improved; if the first gas velocity is too large, too much carbon deposition in the micropores causes some micropores to be blocked and the pore structure to disappear.
[0097] It can be seen from Examples 1 and 6-7 that if the second gas velocity is too small, the carbon deposition rate at the micropore mouth is slow and the mouth shrinkage is not obvious; if the second gas velocity is too large, the carbon deposition rate at the micropore mouth is too fast, the mouth is quickly blocked and closed by carbon deposition, and the pore structure disappears.
[0098] It can be seen from Example 1 and Examples 8-9 that if the first temperature is too low, the carbon source gas cannot reach the pyrolysis temperature, resulting in the inability of carbon deposition; if the first temperature is too high, the excessively high temperature will cause the pore mouth to shrink prematurely, and the carbon after pyrolysis cannot be deposited inside the micropores, thereby failing to achieve the purpose of shallowing the pore depth.
[0099] It can be seen from Examples 1 and 10-11 that if the second temperature is too low, the temperature is insufficient and the effect of shrinking the orifice is not obvious; if the second temperature is too high, the carbon source gas is pyrolyzed quickly, the orifice shrinks quickly, and the carbon that continues to deposit around the orifice will block the orifice.
[0100] It can be seen from Example 1 and Comparative Example 1 that if the first gas velocity is greater than the second gas velocity, too much carbon is deposited, so that the micropores are completely filled with deposited carbon, and the purpose of improving the micropore structure cannot be achieved.
[0101] It can be seen from Example 1 and Comparative Example 2 that if the first carbon source gas is not introduced in step (2), that is, the first carbon deposition is not performed, the pore depth is too large, and no carbon deposition fills part of the space in the micropores. This is not conducive to the deposition of sodium clusters in the micropores, and the specific capacity of the prepared sodium ion battery decreases. At the same time, it is not conducive to the pore shrinkage in the next step, resulting in a small first efficiency.
[0102] It can be seen from Example 1 and Comparative Example 3 that if the second carbon source gas is not introduced in step (2), that is, the second carbon deposition is not performed, the pore size of the micropores is not adjusted, the specific surface area is too large, and the SEI film formation during the battery cycle consumes too much electrolyte, resulting in the sodium ion battery having a low first cycle coulombic efficiency.
[0103] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a modified coal-based hard carbon negative electrode material, characterized in that: The preparation method comprises the following steps: (1) Carbonizing the raw coal to obtain a coal-based hard carbon material with a porous structure; (2) placing the coal-based hard carbon material with a porous structure in a chemical vapor deposition device, introducing a first carbon source gas at a first gas velocity, and maintaining a constant temperature T1 at a first temperature, so that carbon deposition is performed in the micropores of the coal-based hard carbon material, and then introducing a second carbon source gas at a second gas velocity, and maintaining a constant temperature T2 at a second temperature, so that carbon deposition is performed at the micropores of the coal-based hard carbon material, and after completion, the modified coal-based hard carbon negative electrode material is obtained; Wherein, the first gas speed is less than the second gas speed.
2. The preparation method according to claim 1, characterized in that: The raw coal in step (1) includes any one of anthracite, lean coal, lean coal, coking coal, fat coal, gas coal, slightly sticky coal, non-sticky coal, long flame coal or lignite, or a combination of at least two thereof; And / or, the temperature of the carbonization treatment in step (1) is 1100-1400°C; And / or, the carbonization treatment time in step (1) is 1-10 hours.
3. The preparation method according to claim 1, characterized in that: The coal-based hard carbon material with a porous structure in step (1) has an average pore size of 1-4 nm and a pore volume of 0.1-0.3 cm 3 / g; And / or, the coal-based hard carbon material with a porous structure in step (1) has a N2 specific surface area of 300-600m 2 / g; And / or, the CO2 specific surface area of the coal-based hard carbon material with a porous structure in step (1) is 100-200m 2 / g.
4. The preparation method according to claim 1, characterized in that: Step (2) the first gas velocity is 10-50 mL / min; And / or, in step (2), the second gas velocity is 100-300 mL / min, preferably 120-240 mL / min; And / or, in step (2), the first carbon source gas and the second carbon source gas each independently include any one of methane, acetylene, ethane, propane or benzene, or a combination of at least two thereof; And / or, in step (2), the kinetic diameters of the gas molecules of the first carbon source gas and the second carbon source gas are independently 0.4-0.5 nm.
5. The preparation method according to claim 1, characterized in that: Step (2) the first temperature is 600-900°C, T1 is 2-4h; And / or, in step (2), the second temperature is 1000-1200° C., and T2 is 10-30 min.
6. The preparation method according to claim 1, characterized in that: After carbon deposition in the micropores of the coal-based hard carbon material in step (2), the pore volume of the micropores is reduced to 0.02-0.06 cm 3 / g; And / or, after carbon deposition is performed at the micropore openings of the coal-based hard carbon material in step (2), the opening size of the micropores is 0.3-0.5 nm.
7. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: (a) crushing the raw coal to a particle size D50 of 4-30 μm, and then carbonizing it in an inert atmosphere, wherein the carbonizing temperature is 1100-1400°C, the heating rate is 1-10°C / min, and the carbonizing time is 1-10 h, to obtain a coal-based hard carbon material with a porous structure, wherein the average pore size of the coal-based hard carbon material with a porous structure is 1-4 nm, and the pore volume is 0.1-0.3 cm 3 / g, N2 specific surface area is 300-600m 2 / g, CO2 specific surface area is 100-200m 2 / g; (b) placing the coal-based hard carbon material having a porous structure in a chemical vapor deposition device, introducing a first carbon source gas at a first gas rate of 10-50 mL / min and an inert protective gas at a rate of 50-150 mL / min, and maintaining a constant temperature T1 at a first temperature, so that carbon deposition is performed in the micropores of the coal-based hard carbon material, and the pore volume of the micropores is 0.02-0.06 cm 3 / g, then introduce a second carbon source gas at a second gas velocity of 100-300 mL / min and an inert protective gas at a velocity of 200-500 mL / min, and keep the temperature T2 constant at the second temperature, so that carbon deposition is carried out at the micropore openings of the coal-based hard carbon material, and the pore volume of the micropores is 0.01-0.03 cm 3 / g, the pore size of the micropores is 0.3-0.5nm, and after completion, the modified coal-based hard carbon negative electrode material is obtained; Among them, the first gas velocity is less than the second gas velocity, the kinetic diameters of the gas molecules of the first carbon source gas and the second carbon source gas are each independently 0.4-0.5 nm; the first temperature is 600-900°C, T1 is 2-4h; the second temperature is 1000-1200°C, T2 is 10-30min.
8. A modified coal-based hard carbon negative electrode material, characterized in that: The modified coal-based hard carbon negative electrode material is prepared by the preparation method according to any one of claims 1 to 7; The N2 specific surface area of the modified coal-based hard carbon negative electrode material is 2-5 m 2 / g; The CO2 specific surface area of the modified coal-based hard carbon negative electrode material is 0-10m 2 / g.
9. A negative electrode plate, characterized in that: The negative electrode plate comprises the modified coal-based hard carbon negative electrode material as claimed in claim 8.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises the negative electrode sheet as claimed in claim 9.
Citation Information
Patent Citations
Method for producing high-energy-density hard carbon negative electrode and sodium ion battery
CN116573631A
Preparation method and application of gradient sub-nanopore structure hard carbon material
CN117800318A
Sodium-ion battery slurry, negative pole piece and sodium-ion battery
CN118572045A
Cathode based on screening type carbon and battery
CN118579784A
MOF (Metal Organic Framework) derived screening type carbon sodium battery negative electrode material as well as preparation method and application thereof
CN119059513A
Cited By
Lignin-based hard carbon negative electrode material and preparation method and application thereof
CN121134728A